2023
DOI: 10.1109/tits.2023.3235774
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Platoon Formation of Connected and Autonomous Vehicles: Toward Efficient Merging Coordination at Unsignalized Intersections

Abstract: This paper presents a Vehicle-Platoon-Aware Bi-Level Optimization Algorithm for Autonomous Intersection Management (VPA-AIM) to coordinate the merging of Connected and Automated Vehicles (CAVs) at unsignalized intersections. The constraint-coupled bi-level optimization is operated with a limited view of incoming traffic using the rolling horizon procedure to reduce computational complexity. In each decision step, the platoon formation scheme is incorporated into an upperlevel traffic scheduling model as decisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…• Safety: AI can significantly reduce accidents by eliminating human error, leading to safer roads. • Traffic Flow: Platooning [4] and efficient routing can ease congestion and improve efficiency. AI in autonomous vehicles is poised for a bright future, shaping everyday life and creating exciting opportunities.…”
Section: Benefits Of Ai Algorithms For Autonomous Vehiclesmentioning
confidence: 99%
“…• Safety: AI can significantly reduce accidents by eliminating human error, leading to safer roads. • Traffic Flow: Platooning [4] and efficient routing can ease congestion and improve efficiency. AI in autonomous vehicles is poised for a bright future, shaping everyday life and creating exciting opportunities.…”
Section: Benefits Of Ai Algorithms For Autonomous Vehiclesmentioning
confidence: 99%
“…Jiang et al [20] formulated a mixed-integer linear programming model to optimize the passing order and size of platoons. Similarly, Deng et al [21] devised a traffic schedule model to coordinate platoons, introducing platoon formation decision variables. Similar research endeavors can be found in the literature [19,22,23].…”
Section: Introductionmentioning
confidence: 99%